Agent-based tutoring systems by cognitive and affective modeling - Viccari; Jaques; Verdin (Information Science Reference, 2008)
"This book presents a modern view of intelligent tutoring, focusing mainly on the conception of these systems according to a multi-agent approach and on the affective and cognitive modeling of the student in this kind of educational environment"--Provided by publisher.